2019
DOI: 10.1007/s42235-019-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth of TiO2 Nanotube on Titanium Substrate to Enhance its Biotribological Performance and Biocorrosion Resistance

Abstract: TiO2 nanotubes (NTs) have a great potential in improving the osetointegration of titanium (Ti)-based biomaterials. Much efforts have been made to evaluate the biological performance of the TiO2 nanotube in regulating protein adsorption and cells attachments. As often used in orthopaedic applications, although biotribological performance and biocorrosion are important issues in these applications, few researches have been reported on the biotribological performance of NT layers. This paper reports the preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…To date, considering the growth of the nano-thick oxide film ( Figure 8 (c)) in the Ti/TNTs interface ( Figure 8 (b): ox 1 to ox 2 , as observed elsewhere [ 290 , 320 , 334 ]) together with the existence of tribofilm-laminated porous walls on top of the TNTs ( Figure 8 (d)), the fitting model as shown in Figures 8 (e) and 8(f) has been shown to be the most appropriate electronic fitting (lowest accuracy) ever reported for the anodised titanium [ 144 , 286 , 330 , 332 ].…”
Section: Current Challenges In Using Tio 2 Anodic Layermentioning
confidence: 83%
See 4 more Smart Citations
“…To date, considering the growth of the nano-thick oxide film ( Figure 8 (c)) in the Ti/TNTs interface ( Figure 8 (b): ox 1 to ox 2 , as observed elsewhere [ 290 , 320 , 334 ]) together with the existence of tribofilm-laminated porous walls on top of the TNTs ( Figure 8 (d)), the fitting model as shown in Figures 8 (e) and 8(f) has been shown to be the most appropriate electronic fitting (lowest accuracy) ever reported for the anodised titanium [ 144 , 286 , 330 , 332 ].…”
Section: Current Challenges In Using Tio 2 Anodic Layermentioning
confidence: 83%
“…The production process of anodised titanium via two-step AO is now common practice in order to produce a bio-functionalised and reliable passivation of TiO 2 with higher degrees of mechanical stability [92,93,164,298,320,355,356]. Bartkowiak et al [355] suggested a U-shaped layering of TNTs derived from two-step anodisation produced a highly adherent TNTs to the substrate.…”
Section: Future Trend Of the Anodised Titanium In The Implant's Coating Evolutionsmentioning
confidence: 99%
See 3 more Smart Citations